A comparative study of cross-cultural gratitude strategies among Hausa, the case of Arab and Chinese students - Isyaku, Hassan; Yuepeng, Ma; Mahdi, Qusay; Sarhan, Gassan; Salih, Nahid; Paramasivan, Shamala (Australian International Academic Centre, 2016)
The research investigated the thanking/gratitude strategies of three distinct cultures; Hausa, Chinese and Arabic languages with the aim of finding out the different strategies used by them and how different they are in their use of such strategies. The study employs Cheng (2005) Taxonomy of gratitude strategies in analyzing the data which was obtained from 15 participants among the Hausa, Chinese and Arabic students in UPM through the use of DCT (discourse completion Task) which were translated by the researchers into the three languages respectively before retranslated in to English language for analysis. The findings show a significant relationship in the use of “Simple Thanking strategy” among the three cultures as this strategy is utilized in 71.60% of the responses in the Hausa version of the DCT, 62% of the Arabian responses in the Arabic version of their DCT and 63.75% of the responses in the Chinese version of the DCT and were all found to be in the “thanking alone and thanking followed by the favor strategies” consistently. While the least used strategy is the “recognition of imposition” which was only realized by Arabian students and none was found among the Hausa and the Chinese students.